The Implementation Of K-W-L (Know-Want To Know Learned) Strategy To Improve Students’ Arabic Text Reading Ability Of Grade Xi Of MA Bahrul Ulum - Afkhoriyatul Hilmi; Imam Asrori; Nur Anisah Ridwan (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
This research aims to describe: (1) The implementation of K-W-L strategy to improve reading ability of Arabic texts of grade XI students of MIA MA Bahrul Ulum, (2) The improvement of learning outcomes of reading Arabic text of XI graders of MIA MA Bahrul Ulum Tajinan after the implementation of K-W-L strategy. The study used the action research design. The subject was MA Bahrul Ulum Tajinan, because the Arabic language learning ian this school has not been running optimally. The selection of students of grade XI Mathematics and Science program was because the students of grade XI already have a lot of vocabulary and good understanding of qowaid. The study consisted of two cycles and each cycle consisted of stage of (1) planning, (2) implementation, (3) observation, and (4) reflection. The results of the study were that the K-W-L strategy was implemented by activating students to reveal preliminary knowledge related titles, guessing the contents of the text, and discovering new information after reading the text. The implementation of the K-W-L strategy improved the ability of students to read Arabic text by 16 points from the average of 67 to 83 with the mastery score of 95.5%.